The JAK Inhibitor Tofacitinib Rescues Intestinal Barrier Defects Caused by Disrupted Epithelial-macrophage Interactions. (10th September 2020) - Spalinger, Marianne R; Sayoc-Becerra, Anica; Ordookhanian, Christ; Canale, Vinicius; Santos, Alina N; King, Stephanie J; Krishnan, Moorthy; Nair, Meera G; Scharl, Michael; McCole, Declan F
Abstract: Background and Aims: Loss-of-function variants in protein tyrosine phosphatase non-receptor type-2 [ PTPN2 ] promote susceptibility to inflammatory bowel diseases [IBD]. PTPN2 regulates Janus-kinase [JAK] and signal transducer and activator of transcription [STAT] signalling, while protecting the intestinal epithelium from inflammation-induced barrier disruption. The pan-JAK inhibitor tofacitinib is approved to treat ulcerative colitis, but its effects on intestinal epithelial cell-macrophage interactions and on barrier properties are unknown. We aimed to determine if tofacitinib can rescue disrupted epithelial-macrophage interaction and barrier function upon loss of PTPN2. Methods: Human Caco-2BBe intestinal epithelial cells [IECs] and THP-1 macrophages expressing control or PTPN2- specific shRNA were co-cultured with tofacitinib or vehicle. Transepithelial electrical resistance and 4 kDa fluorescein-dextran flux were measured to assess barrier function. Ptpn2 fl/fl and Ptpn2- LysMCre mice, which lack Ptpn2 in myeloid cells, were treated orally with tofacitinib citrate twice daily to assess the in vivo effect on the intestinal epithelial barrier. Colitis was induced via administration of 1.5% dextran sulphate sodium [DSS] in drinking water. Results: Tofacitinib corrected compromised barrier function upon PTPN2 loss in macrophages and/or IECs via normalisation of: [i] tight junction protein expression; [ii] excessive STAT3 signalling; and [iii] IL-6 and IL-22 secretion. In Ptpn2 -LysMCre mice, tofacitinib reduced colonic pro-inflammatory macrophages, corrected underlying permeability defects, and prevented the increased susceptibility to DSS colitis. Conclusions: PTPN2 loss in IECs or macrophages compromises IEC-macrophage interactions and reduces epithelial barrier integrity. Both of these events were corrected by tofacitinib in vitro and in vivo . Tofacitinib may have greater therapeutic efficacy in IBD patients harbouring PTPN2 loss-of-function mutations.